Desain Poster Kampanye Sosial Mitigasi Verbal Abuse - Utomo, M Andhiko; Hidayatullah, Taufan (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2022)
The Covid-19 pandemic affects aspects of life such as shopping, work, to education. Teaching and learning activities that were originally carried out offline or face-to-face have been replaced by online learning. The shift from offline to online has implications for everyone involved, especially children and parents, who play a key role in the continuity of online education. Psychological effects are unavoidable when children or parents study at home. Cases of verbal abuse or verbal abuse of children by parents are increasing. The age of children who experience verbal abuse is 10-12 years old, elementary school education level. Children are trying to understand themselves and compare with their peers at that age. Children will find it difficult to adjust to their environment without parental guidance. Poor communication between parents and children is the cause of verbal abuse. The goal to be achieved is to prevent verbal abuse in children by parents with poster media through Instagram social media to convey information on how to communicate well between mother and child.